Optimal quota for sector-specific immigration - Karin Mayr (Johannes Kepler University of Linz, Department of Economics, 2008)
Sectoral labor supply shortage is a cause of concern in many OECD countries and has raised support for immigration as a potential remedy. In this paper, we derive a general equilibrium model with overlapping generations, where natives require a compensating wage differential for working in one sector rather than in another. We identify price and wage effects of immigration on three different groups of natives: the young working in one of two sectors and the old. We determine the outcome of a majority vote on immigration into a given sector as well as the social optimum. The main findings are that i) the old determine the majority voting outcome of positive immigration into both sectors, if natives are not mobile across sectors, ii) the young determine the majority voting outcome of zero immigration into both sectors, if natives are mobile across sectors, iii) the social optimum is smaller than or equal to the majority voting outcome, and iv) sector-specific immigration is not always a substitute for native mobility across sectors.
Keywords: F22; J31; J61; 330; immigration; political economy; welfare; sectoral mobility; Einwanderung; Migrationspolitik; Arbeitsmobilität; Branche; Allgemeines Gleichgewicht; Pareto-Optimum; Overlapping Generations; Theorie